Exploring EFL Students' Perceptions of Teachers with Native and Non-Native English Accents - Fizza Shakila; Ida Wardani; Istanti Hermagustiana; Desy Rusmawaty (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2026)
A growth in the demand for English language teachers led to a greater number of educators from diverse countries. Therefore, this study investigates EFL students’ perceptions of native English-speaking teachers (NESTs) and non-native English- speaking teachers (NNESTs), with particular attention to how different English accents influence students’ learning experiences. Conducted at a Junior High School in Samarinda, Indonesia, the research adopts a qualitative approach using thematic analysis to interpret data obtained through observations and interviews. The study reveals that students are aware of noticeable differences between native and non-native accents, and these differences impact their comprehension and classroom engagement. While native speakers were often perceived as more fluent and authentic in pronunciation, non-native teachers were seen as more relatable and easier to understand due to their shared linguistic background.